Brennstoff-Lieferfahrzeug des Lebensmittelvereins Zürich (ca. 1950er Jahre; vor dem Gaswerk in Schlieren?)
Verkehr;Landverkehr;Strassenverkehr;Motorfahrzeug;Auto Energie;Energiepolitik (allgemein);Energiewirtschaft;Brennstoff